Pedagogies for Student-Centered Learning : Online and On-Ground - Crumly, Cari; D'Angelo, Sarah; Dietz, Pamela (Book collections on Project MUSE., 2014)
This book will help you to identify the difference between teacher-centered and student-centered learning and the various pedagogies commonly associated with each. This book will draw upon the research and experience of three different educators and their pedagogical variations and uses within the classroom and online. Crumley's synopsis of pedagogies and student-centered learning and suggested action is followed by a collaborative dialogue with Pamela Dietz and Sarah d'Angelo.